Probabilistic power system expansion planning with renewable energy resources and energy storage systems - Choi, Jaeseok; Lee, Kwang Y. (IEEE press series on power engineering, 2021)
"This book presents innovative approaches to the probabilistic planning of generation and transmission systems under uncertainties. It includes renewables and energy storage calculations in using probabilistic and deterministic reliability techniques to assess system performance from a long-term expansion planning viewpoint. It is divided into two sections. The first covers topics related to Generation Expansion Planning (GEP). This includes chapters on cost assessment, methodology and optimization, renewable energy generation, and more. The second part provides information on Transmission System Expansion Planning (TEP). This part explores TEP with reliability constraints, probabilistic production cost simulation for TEP, optimal reliability criteria, and more"--